De la apatía a la vigilancia: la política del desarrollo energético en el Perú - Wise, Carol (2005)
The Peruvian government's lack of commitment in promoting the development of energy projects between 1935 and 1990 resulted in budget deficits and a scarcity of priva te investment in that sector. In the 1990s, this situation started to change. The threshold level was based on new legal agreements. This paper studies the interactions between the Peruvian government, firms and the international institutions in developing the energy market by means of oil and gas exploitation of oil and gas and improved quality services in the electricity sector. The paper also focuses on the quality of management capacities at different levels of government (central and local). lt illustrates the steps taken by the Fujimori government to strike a balance between energy sector management and privatization. To this end, regulatory policies were introduced to establish a climate of confidence between firms and consumers. Furthermore, policies were introduced to protect indigenous communities to forestal! actions that might be harmful to these people when prívate firms began to exploit natural resources in these areas.